Arabidopsis Myosin XI: A Motor Rules the Tracks. Issue 3 (18th September 2014) - Cai, Chao; Henty-Ridilla, Jessica L.; Szymanski, Daniel B.; Staiger, Christopher J.
Abstract : A myosin triple knockout mutant has altered cytoskeletal organization and single filament turnover . Abstract: Plant cell expansion relies on intracellular trafficking of vesicles and macromolecules, which requires myosin motors and a dynamic actin network. Arabidopsis ( Arabidopsis thaliana ) myosin XI powers the motility of diverse cellular organelles, including endoplasmic reticulum, Golgi, endomembrane vesicles, peroxisomes, and mitochondria. Several recent studies show that there are changes in actin organization and dynamics in myosin xi mutants, indicating that motors influence the molecular tracks they use for transport. However, the mechanism by which actin organization and dynamics are regulated by myosin XI awaits further detailed investigation. Here, using high spatiotemporal imaging of living cells, we quantitatively assessed the architecture and dynamic behavior of cortical actin arrays in a mutant with three Myosin XI ( XI-1, XI-2, and XI-K ) genes knocked out ( xi3KO ). In addition to apparent reduction of organ and cell size, the mutant showed less dense and more bundled actin filament arrays in epidermal cells. Furthermore, the overall actin dynamicity was significantly inhibited in the xi3KO mutant. Because cytoskeletal remodeling is contributed mainly by filament assembly/disassembly and translocation/buckling, we also examined the dynamic behavior of individual actin filaments. We found that the xi3KO mutant had significantly decreased actin turnover, with a 2-fold reduction in filament severing frequency. Moreover, quantitative analysis of filament shape change over time revealed that myosin XI generates the force for buckling and straightening of both single actin filaments and actin bundles. Thus, our data provide genetic evidence that three Arabidopsis class XI myosins contribute to actin remodeling by stimulating turnover and generating the force for filament shape change.